SPECIFIC DELIMITATION AND RELATIONSHIP AMONG SPECIES OF DIPLAZIUM BASED ON SPORE MORPHOLOGY - Titien Ngatinem Praptosuwiryo; Masahiro Kato; Dedy Darnaedi (Floribunda, 2007)
pEMBATASAN JENIS DAN HUBUNGAN KEKERABATAN DIANTARA JENIS dIPLAZIUM BERDASARKAN MORFOLOGI SPORA.